(untitled) (Comillas Journal of International Relations, 2021)
This study is based on the existence of a crisis of representative democracy that is evident in a series of factors that affect the stability of the system. This crisis motivates the revision of the concept of democracy and how its foundations have evolved as a result of the development of different models of this form of government. From this perspective, the research attempts to clarify which aspects of liberal democracy and its representative system contradict the classical conception of the term democracy. The analysis of the approaches of the theorists of liberal democracy reveals the creation of a system that breaks with the pillars of classical democracy. This deviation of the liberal model from classical democratic principles is directly related to the causes that led to the outbreak of the crisis. Once the reasons that precipitate the democratic fatigue have been found, a new model of democracy is proposed: dual democracy, which combines aspects of deliberative democracy, direct democracy and the representative system, in an effort to support the transformation of the current system.